Organic Geochemistry and Thermal Maturity Assessment of Cretaceous Balambo Formation from Selected Sites, Kurdistan, NE Iraq - Sarraj, Razawa Hamarashid A.; Mohialdeen, Ibrahim Mohammed J. (Iraqi Journal of Science, 2021)
The Cretaceous Balambo Formation from three sections in Kurdistan Region of Northern Iraq was studied. The selected sections are located in the Zagros Fold -Thrust Belt. Eleven rock samples were analyzed by means of the organic geochemical method, Bitumen extraction method, and gas chromatography/mass spectrometry to determine the bitumen and hydrocarbon content, kerogen types, origin of organic matter, thermal maturity level, and depositional environment. The analyzed samples are considered to have an excellent potential in Baranan-1.G1 and Sazan sections, with poor to fair potential in Baraw section. The Baranan-1.G1 source rocks are of type II kerogen (oil prone), whereas Sazan and Baraw samples are of type II/III (oil/ gas prone). Detailed distribution analysis of biomarkers such as normal alkane, isoprenoids, sterane and terpane was performed on saturated hydrocarbons. The mode of n-alkanes and isoprenoids distribution in all analyzed samples is similar, with a unimodal distribution that indicates non-biodegraded hydrocarbons, with the same range of alkane compounds between C13-C34 alkanes. The results of n-C17, pristane, n-C18 and phytane, and regular steranes show that the source rocks of Balambo Formation in Baranan-1.G1 are mainly rich with algal marine organic matter deposited under a reducing environment, while Baraw and Sazan sections are composed of mixed marine organic matter that refers to terrestrial land plants input deposited under reducing anoxic/dysoxic environments. Thermal maturation appraisal is deduced from Pristane/n-C17 versus Phytane/n-C18 diagram, Carbon Preference Index (CPI), C29 Î²Î²/ (Î²Î²+Î±Î±), C29 20S/ (20S +20R), C32 22S/ (22S+22R), and Ts/ (Ts+Tm). All these parameters indicate that the analyzed samples are mature and have entered the oil window (early to peak oil window). Biomarker ratios of C22/C21, C24/C23 and C26/C25, C31R/C30H show that the Balambo Formation is composed mostly of carbonates with less shale beds.